1987
DOI: 10.1177/019459988709600403
|View full text |Cite
|
Sign up to set email alerts
|

Part II. The Prognostic Significance of Stromal Eosinophilia in Head and Neck Cancer

Abstract: The pathologies of 82 head and neck tumors were examined for histologic features suggestive of poor prognoses. Twelve descriptive histopathologic variables, including two grading scales for malignant tumors, were correlated with DNA flow cytometric data and clinical outcome. We found no correlation between the grading scales and DNA flow cytometric data or clinical outcome. Only one of the histopathologic variables--stromal eosinophilia--was found to significantly correlate with favorable outcome (p = .018). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
8

Year Published

1991
1991
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 12 publications
4
38
2
8
Order By: Relevance
“…The prognostic value of TATE is not put to evidence in his paper. In 1987 [21] and 1992 [22] at last. Goldsmith et al reported on 149 squamous-cell carcinomas of the head and neck and concluded that high-grade TATE correlated highly significantly with a favourable clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic value of TATE is not put to evidence in his paper. In 1987 [21] and 1992 [22] at last. Goldsmith et al reported on 149 squamous-cell carcinomas of the head and neck and concluded that high-grade TATE correlated highly significantly with a favourable clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We arbitrarily considered TATE as the presence of more than 2 eosinophils/HPF. Goldsmith et al [21,22] consid ered 5 categories of eosinophilic prominence and found the presence of 5-10 eosinophils/HPF as TATE. Lowe and Fletcher [11] and Looi [19] considered more than 10 eosinophils/HPF as moderate TATE and more than 100 eosinophils/HPF as massive TATE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A participação dos eosinófilos nos processos de deposição e remodelação do tecido conjuntivo em diversas condições fisiológicas e patológicas fundamenta a teoria da possível função "reparadora" dessa célula (MUNITZ e LEVI-SCHAFFER, 2004 Especificamente para os pacientes com CEC de boca, alguns estudos (DORTA et al, 2002;GOLDSMITH et al, 1992;GOLDSMITH et al, 1987) têm demonstrado uma correlação da TATE com prognóstico favorável, enquanto outros (WONG et al, 1999;HORIUCHI et al, 1993) a relacionam com um prognóstico desfavorável.…”
Section: Discussionunclassified
“…Contudo, muitos trabalhos (HORIUCHI et al, 1993;GOLDSMITH et al, 1992;GOLDSMITH et al, 1987) (ROSENBERG, 2008;NAVARRO et al, 2008;DYER e ROSENBERG, 2006;CARRERAS et al, 2005;BYSTROM et al, 2002;ZHANG e ROSENBERG, 2000;VENGE et al, 1999;DOMACHOWSKE et al, 1998;VENGE e BYSTROM, 1998; ROSENBERG e DYER, 1995).…”
Section: Eosinofilia Tecidual Associada Aos Tumores (Tate)mentioning
confidence: 99%